Near-term spatial hydrologic forecasting in Everglades, USA for landscape planning and ecological forecasting. (October 2020) - Pearlstine, Leonard G.; Beerens, James M.; Reynolds, Gregg; Haider, Saira M.; McKelvy, Mark; Suir, Kevin; Romañach, Stephanie S.; Nestler, Jennifer H.
Abstract: Operational ecological forecasting is an emerging field that leverages ecological models in a new, cross-disciplinary way – using a real-time or nearly real-time climate forecast to project near-term ecosystem states. These applications give decision-makers lead time to anticipate and manage state changes that degrade ecosystem functions or directly impact humans. The Everglades Forecasting model (EverForecast) is an operational forecast model designed specifically for conservation management purposes including water management. It provides up to six-month forecasts of daily projected, spatially continuous stage values across the Everglades. We validated EverForecast quarterly to measured historical values at 207 gages (Jan 1, 2000–Dec 31, 2019). The EverForecast hindcasts of water stage accurately captured measured stage variation, with a low percentage of measured stages exceeding hindcasted values. Over the whole spatial extent, the mean RMSE is 20.98 cm, the mean MAE is 14.42 cm, and the mean MBE is 0.91 cm. Highlights: EverForecast provides near-term forecasts for natural resource management. Daily projected, spatially continuous stage values across the Everglades, Florida. Stochastic results produce a range of forecasts for modeling ecological response. Model highlights management targets to benefit a suite of ecological communities.